Idiomer som står mitt hjerte nær. En korpusbasert analyse av utvalgte idiomer med komponent ’hjerte’ i norsk - Dziurewicz, Elżbieta (Folia Scandinavica Posnaniensia, 2016)
The article presents an exemplary corpus-based analysis of selected Norwegian idioms in order to gain insight into their theory and actual use. The analysis comprises nine frequent idioms with the component 'heart'. First, each idiom is analyzed using the Leksikografisk bokmålskorpus and Oslo-korpuset av taggende norske tekster in terms of: frequency, possible variants and modifications. Next, the results are compared with the lexicographic description from Norwegian dictionary Bokmålsordboka. The main purpose of this chapter is thereby to show the potential of the corpus-based approach in the studies of idiomatic expressions.